Correct positioning of pedicle screws with a percutaneous minimal invasive system in spine trauma - Tinelli, Marco; Matschke, Stefan; Adams, Michael A.; Grützner, Paul Alfred; Münzberg, Matthias; Höppchen, Arnold (Orthopaedics & traumatology, 2014)
Background - When performing minimally invasive spine surgery in trauma patients, a short operation time and a perfect positioning of pedicle screws are demanded. In this study, we show that a Minimally Invasive Pedicle Screw System allows both. - Methods - One hundred and twenty-one patients (131 fractures) with fractures between Th 3 and L 5 were treated. The most common fracture type was A3. We treated 52 females and 69 men with a mean age of 56.7 years. In 72% of the cases, the procedure was performed by two experienced spine surgeons. Postoperatively, all patients were examined using a CT-scan. In 61 patients, an anterior stabilization was additionally performed in 33 patients, vertebroplasty or cyphoplasty was performed. Fifteen patients underwent laminectomy. - Results - No patient postoperatively developed any additional neurological compromise. In total, 682 screws were placed. In the postoperative CT-scan, we found 16 screws (2.2%) in suboptimal position, 8 with medial and 8 with lateral deviation. - Discussion - With the Minimally Invasive Pedicle Screw System used in this study, spinal fractures can be treated in a short operation time with percutaneous stabilization and a correct positioning of the pedicle screws in almost 98%. In our study, no screw was so much malpositioned that revision surgery would have been necessary. - Level of evidence - Level III - Case-control study.